Effects of locomotor muscle fatigue on joint specific power production during cycling - Elmer, S. J.; Marshall, C. S.; Wehmanen, K.; Amann, M.; McDaniel, J.; Martin, D. T.; Martin, J. C. (Medicine & Science in Sports & Exercise, 2012)
Previous authors have reported reductions in maximum power after high-intensity cycling exercise. Exercise-induced changes in power produced by ankle, knee, and hip joint actions (joint-specific powers), however, have not been reported.